Essential clinical anesthesia review : keywords, questions and answers for the boards - Aglio, Linda S.; Lekowski, Robert W.; Urman, Richard D.; Cambridge eBooks (Cambridge : Cambridge University Press, 2015)
This concise, evidence-based board review book, organized according to the ABA keyword list, covers all the fundamental concepts needed to pass written and re-certification board examinations. Each chapter begins with a case scenario or clinical problem from everyday practice, followed by concise discussion and clinical review questions and answers. Discussion progresses logically from preoperative assessment and intraoperative management to postoperative pain management, enhancing the reader's knowledge and honing diagnostic and clinical management skills. New guidelines and recently developed standards of care are also covered. Serving as a companion to the popular textbook Essential Clinical Anesthesia, this resourceful work reflects the clinical experiences of anesthesia experts at Harvard Medical School as well as individually known national experts in the field of anesthesiology. This practical review is an invaluable resource for anesthesiologists in training and practice, whether studying for board exams or as part of continuing education and ABA recertification.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Anesthesia -- Examinations, questions, etc; Anesthesiology -- Examinations, questions, etc; Electronic books